Parameter optimization for a multiaxial stress-strain correction scheme - Lang, Holger; Dressler, Klaus; Pinnau, René (2005)
A gradient based algorithm for parameter identification (least-squares) is applied to a multiaxial correction method for elastic stresses and strains at notches. The correction scheme, which is numerically cheap, is based on Jiang’s model of elastoplasticity. Both mathematical stress-strain analyses (nonlinear finite element method with Jiang’s model of elastoplasticity) and physical strain measurements have been approximized. The gradient evaluation with respect to the parameters, which is very large in scale, is realized by the automatic forward differentiation techniqu
UnivIS-Import:2016-06-30:Pub.2005.tech.FT.ltd.parame
Keywords: Jiang’s model of elastoplasticity; multiaxial high cycle fatigue analysis; durability; parameter identification; automatic differentiation; AD; sensitivities